Ecosystem Services of Chilean Sclerophyllous Forests and Shrublands on the Verge of Collapse: A Review - Alaniz-Baeza, A (Academic Press, 2023)
Dryland forests are the areas most threatened by climate change, urbanization and land-use change simultaneously. Ecosystem services provided by Mediterranean dryland forests are have been in steep decline, and are extensively studied in the Mediterranean basin, however considerably less in other areas with Mediterranean climates. Knowledge of these services is necessary for the promotion of their conservation and restoration. Here, we synthesize current knowledge regarding the main ecosystem services provided by Chilean Mediterranean sclerophyllous forests and shrublands (SFSh). This knowledge allows for the valuation of SFSh in order to conserve, restore and study them. We found 158 studies, including technical reports, theses, and scientific literature regarding the social and environmental benefits derived from Chilean SFSh, though many did not use the term “ecosystem services” (ES). We found data on 19 ecosystem services with four or more studies per service. ES studies in Chile increased in number a couple years after Millennium Ecosystem Assessment published its synthesis in 2005. The most frequently reported services were provisioning services, especially medicinal plants and extracts. Despite the advances in knowledge, ecosystem services of SFSh appear to be rarely quantified, most frequently using oversimplified variable indicators. Services related to animal biodiversity, such as pollination and plague control, are poorly known. In recent years social studies of perception and valuation have increased, showing people s high valuation of SFSh. Additional studies are needed especially regarding water regulation and provision, as global warming will significantly reduce water supply in Mediterranean climates. Finally, we reflect on the advances necessary to enhance conservation, restoration and adaptation of ecosystems and their benefits to people, especially considering political, social and scientific factors. © 2023 Elsevier Ltd